2013
DOI: 10.1002/jor.22481
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between muscle fatty infiltration and the biological characteristics and stimulation potential of tenocytes from rotator cuff tears

Abstract: The healing after rotator cuff surgery is still dissatisfying, and increased muscle fatty infiltration even more impairs the healing success. To achieve sufficient healing after rotator cuff reconstructions, the use of growth factors may be one possibility. The aim of the study was to identify a possible relationship between fatty infiltration of the supraspinatus muscle and cellular biological characteristics and stimulation potential of tenocyte-like cells (TLCs). TLCs of 3 donor groups differing in grade of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…However, the cellular or molecular mechanisms behind this relationship are still elusive. We previously showed that TLCs isolated from donors differing in age, sex and MFI exhibit different cellular characteristics and stimulation potential with BMP-2 and BMP-7 [ 18 , 19 , 20 ]. Since MMPs and TIMPs represent the main regulators of modeling and remodeling in the tendon, it was the aim to assess their expression and secretion in TLCs and their supernatant, related to the age, sex and degenerative status of the tendon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cellular or molecular mechanisms behind this relationship are still elusive. We previously showed that TLCs isolated from donors differing in age, sex and MFI exhibit different cellular characteristics and stimulation potential with BMP-2 and BMP-7 [ 18 , 19 , 20 ]. Since MMPs and TIMPs represent the main regulators of modeling and remodeling in the tendon, it was the aim to assess their expression and secretion in TLCs and their supernatant, related to the age, sex and degenerative status of the tendon.…”
Section: Resultsmentioning
confidence: 99%
“…It might be possible that the presence of immune cells such as macrophages or lymphocytes could have affected the results of the study, because they are also able to express MMPs and TIMPs. However, as we could show previously, the tenocyte cultures isolated with the same method were characterized by flow cytometry analysis and expressed hematopoietic markers (CD11b, CD14, CD19, CD34, CD45) in less than 2% [ 18 , 19 , 20 ]. Therefore, the presence of immune cells in the tenocyte cultures can be nearly ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…Fat infiltration and ossification are pathological signs of tendon degeneration [46]. The differentiation into non-tenocytes is known to induce degenerative processes, which can later manifest as lipid depositions and calcified tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies to date have attempted to modify disease progression or improve healing by adjusting the expression of the fibrotic mediators that was found to be remarkable in diseased tendons, without a comprehensive understanding of their role and mechanisms in the development of the disease. Cells from clinical samples of tendinopathy show an altered phenotype [45] and the cellular activities of RC tear tendon cells may likewise differ according to the severity of the disease [46]. Despite these differential cellular responses, the majority of in vitro tendinopathy studies have not taken this into account.…”
Section: Discussionmentioning
confidence: 99%